2021
DOI: 10.3389/fmicb.2021.682255
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Phage Therapy in a Murine Model of Pseudomonas aeruginosa Pneumonia and Sepsis

Abstract: The emergence of multi-drug resistant Pseudomonas aeruginosa necessitates the search for treatment options other than antibiotic use. The use of bacteriophages is currently being considered as an alternative to antibiotics for the treatment of bacterial infections. A number of bacteriophages were introduced to treat pneumonia in past reports. However, there are still lack of knowledge regarding the dosages, application time, mechanism and safety of phage therapy against P. aeruginosa pneumonia. We used the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
3
18
0
1
Order By: Relevance
“…P. aeruginosa, a Gram-negative, widespread, multidrug-resistant pathogen causes complex diseases that are difficult to cure ( Azam and Khan, 2019 ). In recent years, phages have received increasing attention, and are believed to replace antibiotics as a solution to antibiotic resistance in bacteria ( Yang et al, 2021 ). Previous studies have shown that phage infection inhibits bacterial growth, which increases with increasing MOI ( Imam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa, a Gram-negative, widespread, multidrug-resistant pathogen causes complex diseases that are difficult to cure ( Azam and Khan, 2019 ). In recent years, phages have received increasing attention, and are believed to replace antibiotics as a solution to antibiotic resistance in bacteria ( Yang et al, 2021 ). Previous studies have shown that phage infection inhibits bacterial growth, which increases with increasing MOI ( Imam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 Yang et al demonstrated that inhaled phage KPP10 exerted a significant protective effect against pneumonia caused by P. aeruginosa D4. 21 Morello et al demonstrated that two different bacteriophages (PAK-P3 and P3-CHA) administered intranasally are effective in treating lung infections by two different P. aeruginosa strains. 22 Forti et al demonstrated a broad-range bacteriophage cocktail (PYO2, DEV, E215, E217, PAK_P1 and PAK_P4) can reduce P. aeruginosa biofilms and treat acute infections in two animal models (Galleria larva and mice).…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have highlighted the use of phages to control biofilm-forming bacteria, including P. aeruginosa and demonstrated the ability of phages to eradicate the P. aeruginosa infections [28,29] and biofilm-forming bacterial cells [16,[30][31][32][33]. However, previous studies have focused mainly on the treatment of cystic fibrosis caused by P. aeruginosa by phages in vivo [29,[34][35][36]. Moreover, using phage therapy against MDR P. aeruginosa in wound infection shows high efficacy and safety through topical and oral administrations [29,[37][38][39].…”
mentioning
confidence: 99%